Antecedents of an Inclusive Leader in Public Organizations: A Macro and Micro Perspective - Namrta Sharma; Meghna Sabharwal (Journal of Social Equity and Public Administration)
As public administration struggles to further the goal of social equity, part of the problem is leaders who do not know what characteristics can help them act more inclusively. The role of a leader to establish and promote social equity cannot be overemphasized. Leaders can inadvertently play saboteur. As humans, leaders suffer from cognitive limitations that translate into alienating behaviors toward groups of employees, citizens, and other stakeholders. With complex internal battles to fight, what are the antecedents that motivate a leader to emerge as an inclusive leader? This article aims to create a comprehensive conceptual framework for an inclusive leader. We examine these precursors in a broader context of community and society relevant to public administration with the aim to inform research, practice, and teaching in the field.